Integration of life cycle assessment and life cycle costing within a BIM-based environment - Viscuso, Salvatore; Monticelli, Carol; Ahmadnia, Amirhossein; Zanelli, Alessandra (Frontiers in Sustainability, 2022)
A Building Information Modelling (BIM)-integrated workflow for quantifying and assessing the environmental and economic impacts during the life cycle of buildings is presented and deepened in this essay. With the support of digital methods and informative building models, these impacts can be scored through the analysis of variants and their weighted comparison. Through an optimized computational code, the semiautomatic calculation can directly link the results with the visualization tools (dashboards and coloured 3D models), thus accelerating – and making it more accessible – the optioneering of multiple design alternatives during the project development.